(untitled) (Vietnam Journal of Community Medicine, 2024)
Effective airway management and ensuring adequate ventilation for tracheal surgery are always challenges for anesthesiologists. At Bach Mai Hospital, we successfully anesthetized and operated on a 57-year-old male patient with a tumor in the lower part of the trachea (size 21 × 17 × 31 mm, mainly attached to the right wall near the carina). Following induction, we performed oral tracheal intubation above the tumor and opened the right chest to access the trachea. Once we opened the tracheal wall to access the tumor, we inserted an endotracheal tube through the surgical field to establish ventilation of the left lung. However, after 5 minutes, the oxygen saturation decreased to 80-82% (with FiO2 100% and PEEP 10 cmH2O). The surgeon then inserted a 14-Fr nasogastric tube through the surgical field to apply continuous positive airway pressure to the right main bronchus, using 100% oxygen at a pressure of 5-6 cmH2O and a flow rate of 6-7 liters/minute. During tracheobronchial reconstruction, the oxygen saturation was maintained at 95-98%. Then, the surgeon removed the continuous positive airway pressure system and the endotracheal tube from the left main bronchus, closed the tracheobronchial wall, and re-ventilated the two lungs through the oral endotracheal tube. One day after the surgery, the patient was extubated and discharged on the sixth day after the surgery.